Effectiveness of Mycorrhizal Fertilizer on Soil Quality, Growth, and Yield of Upland Rice in Ultisol Soil - Mulyadi, Mulyadi; Sari, Shabilla Amartiya; Rusdan, Risna (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2026)
Rice production in Ultisol land is often hindered by low soil fertility, which limits the availability of nutrients and crop productivity. This research aimed to examine the effectiveness of various doses of mycorrhizal biofertilizer on improving soil quality, growth, and yield production of upland rice (Oryza sativa L.) in Ultisol soil. This experiment used mycorrhizal fertilizer (Mycogrow). The research used a Completely Randomized Design with four mycorrhizal dose treatments: M0 (control, no mycorrhiza), M1 (15 g of mycorrhiza polybag⁻¹), M2 (30 g of mycorrhiza polybag⁻¹), and M3 (45 g of mycorrhiza polybag⁻¹) with three replications, three plant samples using polybag 40 cm x 40 cm and each polybags containing 10 kg of soil for cultivating the Trisakti rice. The results showed that the application of mycorrhiza at the M3 (45 g of mycorrhiza polybag⁻¹) dose significantly improved the physical and chemical properties of the soil, such as reducing bulk density, increasing porosity, pH, soil organic matter content, and the availability of nitrogen, available phosphorous, and available potassium. During the vegetative and generative phase, the M3 (45 g of mycorrhiza polybag⁻¹) is the best treatments in increasing plant height, tiller number, flag leaf area, SPAD value, panicle number, panicle length, flowering time, and 1000-grain weight. Therefore, mycorrhiza application can be recommended as a sustainable and environmentally friendly fertilization technology.